PERANCANGAN SISTEM INFORMASI MONITORING ANTRIAN PEMBAYARAN KULIAH PADA LKM PERGURUAN TINGGI RAHARJA - Asep Saefullah; Nur Azizah; Andri Ansyah (Universitas Raharja, 2015)
A student can make the payment of tuition fees by bank transfer mechanism and only takes a few seconds to send money from one account to another account. But sometimes the payment of tuition fees is not always through the transfer, there is also the payment must come to the checkout or cashier. At this time information technology has become more advanced, the activity came to the counter and make payment by way of queuing is an activity that is uncomfortable and a waste of time. Perguruan Tinggi Raharja payment systems still use manual way is to make payments directly to the cashier in this case LKM (Layanan Keuangan Mahasiswa), and often long queues at the deadline for payment. It is necessary for the proper solution of an information system in addressing the queue. This research is to design and create an information system that aims to help parse avoid long queues at the time of payment in the LKM. The design study began on the process of data collection, analysis of the problem, designing a program using the PHP language (Hypertext Prepocessor), MySQL database with prototype research methods. Results from this study in the form of a monitoring system that can monitor the movement queuing number of students so that when the queue no longer need to stand in front of the LKM, students can perform other activities and only occasionally see on the display the number the number of students queued.